The Personal Discount Rate: Evidence from Military Downsizing Programs - Warner, John T; Pleeter, Saul (American Economic Review, 2001)
The military drawdown program of the early 1990's provides an opportunity to obtain estimates of personal discount rates based on large numbers of people making real choices involving large sums. The program offered over 65,000 separatees the choice between an annuity and a lump-sum payment. Despite break-even discount rates exceeding 17 percent, most of the separatees selected the lump sum—saving taxpayers $1.7 billion in separation costs. Estimates of discount rates range from 0 to over 30 percent and vary with education, age, race, sex, number of dependents, ability test score, and the size of payment. (JEL D91)